High-strength flame-retardant ultraviolet curing adhesive and preparation process
By using acrylate naphthyl DOPO flame retardant and photocuring crosslinking reaction in polyurethane photocuring adhesive, the problem of insufficient flame retardant and heat resistance of polyurethane adhesive is solved, and its flame retardant performance is significantly improved. Mechanical properties.
Patent Information
- Application Number
- CN202411416180.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-24
AI Technical Summary
Existing polyurethane photocuring adhesives lack flame retardant and heat resistance, especially the poor compatibility of DOPO with polyurethane materials, which affects the mechanical properties.
Using aqueous polyurethane acrylate as the main material, adding acrylate naphthyl DOPO flame retardant, prepared by microwave coupling reaction, combined with photocuring crosslinking reaction, forming a stable chemical crosslinking network, improving the crosslinking degree of polyurethane molecular chain and Heat resistance.
The flame retardant performance, heat resistance, tensile strength and hardness of polyurethane adhesives are significantly improved, and the peak heat release rate and total heat release amount are reduced, forming a high-strength flame retardant ultraviolet curing adhesive.
Smart Images

Figure CN119177106A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultraviolet light curing adhesives, in particular to a high-strength flame-retardant ultraviolet light curing adhesive and a preparation process. Background Art
[0002] UV-curable polyurethane has the advantages of fast curing speed and environmental protection, and is widely used in adhesives, coatings, etc. In order to solve the problem that polyurethane adhesives are not flame retardant, flame retardants such as phosphorus-containing flame retardants and nitrogen-based flame retardants are usually added to the adhesive. Patent CN118108924B discloses a halogen-free flame retardant polyurethane elastomer and a preparation process, using phosphate phthalazinone as a chain extender to introduce a rigid condensed ring structure of phthalazinone with high thermal stability into the polyurethane molecular chain, thereby improving the flame retardancy and heat resistance of the polyurethane elastomer. However, this patent does not improve the mechanical strength of the polyurethane material.
[0003] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO has excellent flame retardancy and can play the role of condensed phase flame retardancy and gas phase flame retardancy. It is widely used in materials such as polyurethane and epoxy resin. However, DOPO has poor compatibility with polyurethane and other material matrices. The addition and blending method has a great influence on the mechanical properties of the material. Moreover, as a phosphorus-based flame retardant, DOPO has a low thermal decomposition temperature, which reduces the heat resistance of the material. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a high-strength flame-retardant UV light-curing adhesive and a preparation process, which solves the problem that the polyurethane light-curing adhesive has poor heat resistance and is not flame-retardant.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a high-strength flame-retardant UV-curing adhesive, comprising the following components in parts by weight, 76-84 parts by weight of water-based polyurethane acrylate, 3-10 parts by weight of acrylate naphthyl DOPO flame retardant, 7-10 parts by weight of active diluent, 0.4-0.8 parts by weight of defoamer, and 2.5-3.5 parts by weight of photoinitiator.
[0006] The preparation method of the acrylate naphthyl DOPO flame retardant is as follows: add xylene solvent, 6-DOPO-2-naphthol, 2,5-diacrylate phthalic acid, and p-toluenesulfonic acid into a reaction bottle, react, concentrate the solution under reduced pressure, perform silica gel column chromatography, and use a mixed solution of ethyl acetate and petroleum ether as the eluent to obtain the acrylate naphthyl DOPO flame retardant. The reaction temperature is controlled at 80-100°C and the reaction time is 4-10h.
[0007] Among them, the ratio of 6-DOPO-2-naphthol, 2,5-diacrylate phthalic acid, and p-toluenesulfonic acid is (2-2.6) mol: 1 mol: (0.12-0.16) mol.
[0008] Among them, the active diluent is tripropylene glycol diacrylate and 1,6-hexanediol diacrylate; the photoinitiator is photoinitiator 1173 or photoinitiator 184; and the defoamer is an organosilicon defoamer.
[0009] The preparation process of 6-DOPO-2-naphthol is as follows: add 1,4-dioxane solvent, DOPO, 6-bromo-2-naphthol, tetrakis(triphenylphosphine)palladium and potassium carbonate into a microwave chemical reactor, react in a nitrogen range, concentrate the solution under reduced pressure, perform silica gel column chromatography separation, and use a mixed solution of dichloromethane and methanol as the eluent to obtain 6-DOPO-2-naphthol. During the reaction, the power of the microwave chemical reactor is controlled to be 300-600W, and the reaction time is 5-10min.
[0010] Among them, the ratio of DOPO, 6-bromo-2-naphthol, tetrakis(triphenylphosphine)palladium and potassium carbonate is 1 mol: (0.8-1.3) mol: (0.05-0.07) mol: (1.6-2.2) mol.
[0011] The preparation process of 2,5-diacrylate phthalic acid is as follows: add dichloromethane solvent, 2,5-dihydroxyphthalic acid and pyridine into a reaction bottle, add acryloyl chloride dropwise in an ice-water bath, and then react at 20-40° C. for 8-12 hours, concentrate the solution under reduced pressure, and separate by silica gel column chromatography, wherein the eluent is a mixed solution of ethyl acetate and petroleum ether, to obtain 2,5-diacrylate phthalic acid.
[0012] Among them, the ratio of 2,5-dihydroxyphthalic acid, pyridine and acryloyl chloride is 1 mol: (2.2-2.5) mol: (2-2.4) mol.
[0013] Among them, the preparation process of the high-strength flame-retardant UV-curing adhesive is: add water, water-based polyurethane acrylate, acrylate naphthyl DOPO flame retardant, active diluent, and defoaming agent into a container, stir and disperse in a high-speed disperser, and then add a photoinitiator to obtain a high-strength flame-retardant UV-curing adhesive.
[0014] Technical effect: The present invention uses tetrakis(triphenylphosphine)palladium as a catalyst, potassium carbonate as a co-catalyst, and microwave irradiation to couple 6-bromo-2-naphthol with DOPO to obtain 6-DOPO-2-naphthol, which is then esterified with 2,5-diacrylate phthalic acid to obtain a new type of acrylate naphthyl DOPO flame retardant.
[0015] The present invention uses waterborne polyurethane acrylate as the main material of the photocurable adhesive, tripropylene glycol diacrylate or 1,6-hexanediol diacrylate as the active diluent, and adds an acrylate naphthyl DOPO flame retardant, which contains two alkenyl groups and can replace part of the active diluent, and undergoes a photocuring cross-linking reaction with the waterborne polyurethane acrylate, thereby grafting the naphthyl DOPO structure into the polyurethane molecular chain. As a reactive flame retardant, the polyurethane adhesive is endowed with excellent combustion charring and flame retardant properties, and the peak heat release rate and total heat release of the adhesive are significantly reduced. In addition, the acrylate naphthyl DOPO flame retardant contains biphenyl and naphthyl condensed ring heat-resistant groups, which are chemically bonded to the polyurethane molecular chain, and can increase the initial thermal decomposition temperature of the polyurethane adhesive, showing better heat resistance.
[0016] The acrylate naphthyl DOPO flame retardant of the present invention undergoes a photocuring crosslinking reaction with waterborne polyurethane acrylate, thereby increasing the crosslinking degree of the polyurethane acrylate molecular chain and forming a stable chemical crosslinking network. In addition, the DOPO flame retardant contains a naphthyl rigid condensed ring group and has high structural stability, which is beneficial to improving the hardness, tensile strength and other mechanical properties of the polyurethane adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the reaction formula for preparing 2,5-diacrylate phthalic acid.
[0018] Figure 2 This is the reaction formula for preparing 6-DOPO-2-naphthol.
[0019] Figure 3 This is the reaction formula for preparing acrylate naphthyl DOPO flame retardant. DETAILED DESCRIPTION
[0020] Embodiments of the present invention are described in detail below, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limitations of the present invention. In the embodiments, if specific techniques or conditions are not indicated, the techniques or conditions described in the document in this area or the product specifications are carried out. Reagents used or instruments that do not indicate manufacturers are conventional products that can be obtained commercially.
[0021] The CAS number of the 2,5-dihydroxyphenylcarboxylic acid of the present invention is 13987-45-6. The CAS number of 6-bromo-2-naphthol is 15231-91-1. DOPO is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and its CAS number is 35948-25-5. The brand of waterborne polyurethane acrylate is UCECOAT 7718.
[0022] Example 1 (1) Add 40 mL of dichloromethane solvent, 8 mmol of 2,5-dihydroxybenzoic acid, and 18.6 mmol of pyridine to a reaction flask, add 19.2 mmol of acryloyl chloride dropwise in an ice-water bath, and then react at 20°C for 12 hours. Concentrate the solution under reduced pressure and perform silica gel column chromatography with a mixed solution of ethyl acetate and petroleum ether as the eluent to obtain 2,5-diacrylatebenzoic acid.
[0023] (2) Add 15 mL of 1,4-dioxane solvent, 5 mmol of DOPO, 4.8 mmol of 6-bromo-2-naphthol, 0.35 mmol of tetrakis(triphenylphosphine)palladium, and 9 mmol of potassium carbonate into a microwave chemical reactor, control the power of the microwave chemical reactor to 300 W, react in a nitrogen atmosphere for 10 min, concentrate the solution under reduced pressure, and separate by silica gel column chromatography using a mixed solution of dichloromethane and methanol as the eluent to obtain 6-DOPO-2-naphthol.
[0024] (3) Add 60 mL of xylene solvent, 13 mmol of 6-DOPO-2-naphthol, 5 mmol of 2,5-diacrylate diphthalic acid, and 0.6 mmol of p-toluenesulfonic acid into a reaction flask, react at 90° C. for 10 h, concentrate the solution under reduced pressure, and separate by silica gel column chromatography using a mixed solution of ethyl acetate and petroleum ether as the eluent to obtain an acrylate naphthyl DOPO flame retardant.
[0025] (4) Add 60 mL of water, 83 g of waterborne polyurethane acrylate, 3 g of acrylate naphthyl DOPO flame retardant, 10 g of active diluent 1,6-hexanediol diacrylate, and 0.5 g of silicone defoamer (brand SQ-XP101) into a container and stir and disperse them in a high-speed disperser. Then add 3.2 g of photoinitiator 1173 to obtain a high-strength flame-retardant UV-curing adhesive.
[0026] Example 2 (1) Add 50 mL of dichloromethane solvent, 8 mmol of 2,5-dihydroxybenzoic acid, and 20 mmol of pyridine to a reaction flask, add 19.2 mmol of acryloyl chloride dropwise in an ice-water bath, and then react at 40°C for 8 hours. Concentrate the solution under reduced pressure and perform silica gel column chromatography with a mixed solution of ethyl acetate and petroleum ether as the eluent to obtain 2,5-diacrylatebenzoic acid.
[0027] (2) Add 20 mL of 1,4-dioxane solvent, 5 mmol of DOPO, 5.5 mmol of 6-bromo-2-naphthol, 0.25 mmol of tetrakis(triphenylphosphine)palladium, and 11 mmol of potassium carbonate into a microwave chemical reactor, control the power of the microwave chemical reactor to 600 W, react in a nitrogen atmosphere for 5 min, concentrate the solution under reduced pressure, and separate by silica gel column chromatography, using a mixed solution of dichloromethane and methanol as the eluent to obtain 6-DOPO-2-naphthol.
[0028] (3) Add 40 mL of xylene solvent, 10 mmol of 6-DOPO-2-naphthol, 5 mmol of 2,5-diacrylate diphthalic acid, and 0.6 mmol of p-toluenesulfonic acid into a reaction flask, react at 100 °C for 4 h, concentrate the solution under reduced pressure, and separate by silica gel column chromatography using a mixed solution of ethyl acetate and petroleum ether as the eluent to obtain an acrylate naphthyl DOPO flame retardant.
[0029] (4) Add 60 mL of water, 84 g of waterborne polyurethane acrylate, 3 g of acrylate naphthyl DOPO flame retardant, 10 g of active diluent 1,6-hexanediol diacrylate, and 0.8 g of silicone defoamer (brand SQ-XP101) into a container and stir and disperse them in a high-speed disperser. Then add 2.5 g of photoinitiator 184 to obtain a high-strength flame-retardant UV-curing adhesive.
[0030] Example 3 (1) Add 50 mL of dichloromethane solvent, 8 mmol of 2,5-dihydroxybenzoic acid, and 17.6 mmol of pyridine to a reaction flask, add 16 mmol of acryloyl chloride dropwise in an ice-water bath, and then react at 30°C for 12 hours. Concentrate the solution under reduced pressure and perform silica gel column chromatography with a mixed solution of ethyl acetate and petroleum ether as the eluent to obtain 2,5-diacrylatebenzoic acid.
[0031] (2) Add 15 mL of 1,4-dioxane solvent, 5 mmol of DOPO, 4 mmol of 6-bromo-2-naphthol, 0.3 mmol of tetrakis(triphenylphosphine)palladium, and 8 mmol of potassium carbonate into a microwave chemical reactor, control the power of the microwave chemical reactor to 300 W, react in a nitrogen atmosphere for 10 min, concentrate the solution under reduced pressure, and separate by silica gel column chromatography using a mixed solution of dichloromethane and methanol as the eluent to obtain 6-DOPO-2-naphthol.
[0032] (3) Add 60 mL of xylene solvent, 13 mmol of 6-DOPO-2-naphthol, 5 mmol of 2,5-diacrylate diphenylcarboxylic acid, and 0.8 mmol of p-toluenesulfonic acid into a reaction flask, react at 80° C. for 10 h, concentrate the solution under reduced pressure, and separate by silica gel column chromatography using a mixed solution of ethyl acetate and petroleum ether as the eluent to obtain an acrylate naphthyl DOPO flame retardant.
[0033] (4) Add 60 mL of water, 83 g of waterborne polyurethane acrylate, 3 g of acrylate naphthyl DOPO flame retardant, 7 g of active diluent tripropylene glycol diacrylate, and 0.4 g of silicone defoamer (brand SQ-XP101) into a container and stir and disperse them in a high-speed disperser. Then add 3.5 g of photoinitiator 1173 to obtain a high-strength flame-retardant UV-curing adhesive.
[0034] The difference between Comparative Example 1 and Example 1 is that no acrylate naphthyl DOPO flame retardant is added, specifically as follows: (1) Add 60 mL of water, 83 g of waterborne polyurethane acrylate, 10 g of active diluent 1,6-hexanediol diacrylate, and 0.5 g of silicone defoamer (brand SQ-XP101) into a container and stir and disperse them in a high-speed disperser. Then add 3.2 g of photoinitiator 1173 to obtain a high-strength flame-retardant UV-curing adhesive.
[0035] The difference between Comparative Example 2 and Example 1 is that 2,5-diacrylate phthalic acid is used instead of acrylate naphthyl DOPO flame retardant, as follows: (1) Add 60 mL of water, 83 g of waterborne polyurethane acrylate, 3 g of 2,5-diacrylate phthalic acid, 10 g of active diluent 1,6-hexanediol diacrylate, and 0.5 g of silicone defoamer (brand SQ-XP101) into a container and stir and disperse them in a high-speed disperser. Then add 3.2 g of photoinitiator 1173 to obtain a high-strength flame-retardant UV-curing adhesive.
[0036] The difference between Comparative Example 3 and Example 1 is that DOPO is used instead of the acrylate naphthyl DOPO flame retardant, as follows: (1) Add 60 mL of water, 83 g of waterborne polyurethane acrylate, 3 g of DOPO, 10 g of active diluent 1,6-hexanediol diacrylate, and 0.5 g of silicone defoamer (brand SQ-XP101) into a container and stir and disperse them in a high-speed disperser. Then add 3.2 g of photoinitiator 1173 to obtain a high-strength flame-retardant UV-curing adhesive.
[0037] The curing conditions of UV-curable adhesives are: the light source is a 1000W high-pressure mercury lamp, the lamp distance is 10cm, and the irradiation time is 90s. The tensile properties of the cured adhesive are tested according to the GB / T 528-2009 method. The hardness of the cured product is tested according to the GB / T 531.1-2008 method. The test results are shown in the table below.
[0038]
[0039] The combustion performance of the cured product was tested using a cone calorimeter. The sample size was 8cm×8cm×0.3cm and the radiation heat flux was 35kW / m 2 .
[0040] The thermal properties and thermal decomposition temperature of the cured product were tested using a thermogravimetric analyzer in a nitrogen atmosphere with a heating rate of 10°C / min. The test temperature ranged from room temperature to 700°C. The test results are shown in the table below.
[0041]
[0042] After testing, compared with Comparative Example 1, Examples 1, 2, and 3 all added acrylate naphthyl DOPO flame retardant, which contains two alkenyl groups and can replace part of the active diluent, and undergo a photocuring cross-linking reaction with waterborne polyurethane acrylate, thereby grafting the naphthyl DOPO structure into the polyurethane molecular chain. As a reactive flame retardant, it gives the polyurethane adhesive excellent combustion charring and flame retardant properties, and significantly reduces the peak heat release rate and total heat release of the adhesive. In addition, the initial thermal decomposition temperature (5% mass loss temperature) of the polyurethane adhesive is significantly improved, and it has better heat resistance, mainly because the acrylate naphthyl DOPO flame retardant contains biphenyl and naphthyl condensed ring heat-resistant groups, which are chemically bonded to the polyurethane molecular chain, which can increase the initial thermal decomposition temperature of the polyurethane adhesive and show better heat resistance.
[0043] Compared with Comparative Example 1, the tensile strength and hardness of the polyurethane adhesives of Examples 1, 2, and 3 are also significantly improved. This is because the acrylate naphthyl DOPO flame retardant undergoes a photocuring cross-linking reaction with the waterborne polyurethane acrylate, which increases the cross-linking degree of the polyurethane acrylate molecular chain and forms a stable chemical cross-linking network. In addition, the DOPO flame retardant contains a naphthyl rigid condensed ring group with high structural stability, which is beneficial to improving the mechanical strength of the polyurethane adhesive.
[0044] Comparative Example 2 uses 2,5-diacrylate phthalic acid instead of acrylate naphthyl DOPO flame retardant, which contains alkenyl and can undergo photocuring crosslinking reaction with polyurethane acrylate, but does not contain DOPO flame retardant group and naphthyl condensed ring structure, and does not have flame retardancy. The peak heat release rate and total heat release of the adhesive are higher than those of Example 1, and the flame retardancy is poor. In addition, the tensile strength and hardness are lower than those of Example 1.
[0045] Comparative Example 3 uses DOPO instead of the acrylate naphthyl DOPO flame retardant. The peak heat release rate and total heat release of the adhesive are significantly lower than those of Comparative Example 1, and the flame retardant performance is significantly improved. However, since DOPO does not contain an olefinic group, it cannot undergo a photocuring crosslinking reaction with polyurethane acrylate, and has poor compatibility with polyurethane acrylate. When added to the polyurethane adhesive, it has an adverse effect on its mechanical properties and reduces the tensile strength and hardness of the adhesive. In addition, DOPO has a phosphate group and a low thermal decomposition temperature. When added to the adhesive, the thermal decomposition temperature and heat resistance of the adhesive are reduced.
[0046] The acrylate naphthyl DOPO flame retardants of Examples 4-7 were all prepared according to the process of Example 1.
[0047] Example 4 Add 60 mL of water, 82 g of waterborne polyurethane acrylate, 4.5 g of acrylate naphthyl DOPO flame retardant, 10 g of active diluent 1,6-hexanediol diacrylate, and 0.5 g of silicone defoamer (brand SQ-XP101) into a container, stir and disperse in a high-speed disperser, and then add 3.2 g of photoinitiator 1173 to obtain a high-strength flame-retardant UV-curing adhesive.
[0048] Example 5 Add 60 mL of water, 80 g of waterborne polyurethane acrylate, 6 g of acrylate naphthyl DOPO flame retardant, 10 g of active diluent 1,6-hexanediol diacrylate, and 0.5 g of silicone defoamer (brand SQ-XP101) into a container, stir and disperse in a high-speed disperser, and then add 3.2 g of photoinitiator 1173 to obtain a high-strength flame-retardant UV-curing adhesive.
[0049] Example 6 Add 60 mL of water, 78 g of waterborne polyurethane acrylate, 8 g of acrylate naphthyl DOPO flame retardant, 10 g of active diluent 1,6-hexanediol diacrylate, and 0.5 g of silicone defoamer (brand SQ-XP101) into a container, stir and disperse in a high-speed disperser, and then add 3.2 g of photoinitiator 1173 to obtain a high-strength flame-retardant UV-curing adhesive.
[0050] Example 7 Add 60 mL of water, 76 g of waterborne polyurethane acrylate, 10 g of acrylate naphthyl DOPO flame retardant, 10 g of active diluent 1,6-hexanediol diacrylate, and 0.5 g of silicone defoamer (brand SQ-XP101) into a container, stir and disperse in a high-speed disperser, and then add 3.2 g of photoinitiator 1173 to obtain a high-strength flame-retardant UV-curing adhesive.
[0051] The combustion performance of the cured product was tested using a cone calorimeter. The sample size was 8cm×8cm×0.3cm and the radiation heat flux was 35kW / m 2 .
[0052] The thermal properties and thermal decomposition temperature of the cured product were tested using a thermogravimetric analyzer in a nitrogen atmosphere with a heating rate of 10°C / min. The test temperature ranged from room temperature to 700°C. The test results are shown in the table below.
[0053]
[0054] Examples 4-7 studied the effects of different amounts of acrylate naphthyl DOPO flame retardant and active diluent 1,6-hexanediol diacrylate on the thermal properties and flame retardant properties of polyurethane adhesives. As the acrylate naphthyl DOPO flame retardant replaced more active diluents, the peak heat release rate and total heat release of the polyurethane adhesive became smaller and smaller, and the combustion charring and flame retardancy of the adhesive became better and better.
Claims
1. A high-strength flame-retardant UV-curing adhesive, characterized in that: The UV-curable adhesive comprises the following components in parts by weight: 76-84 parts by weight of waterborne polyurethane acrylate, 3-10 parts by weight of acrylate naphthyl DOPO flame retardant, 7-10 parts by weight of active diluent, 0.4-0.8 parts by weight of defoamer, and 2.5-3.5 parts by weight of photoinitiator; The preparation method of the naphthyl acrylate DOPO flame retardant is as follows: adding xylene solvent, 6-DOPO-2-naphthol, 2,5-diacrylate phthalic acid and p-toluenesulfonic acid into a reaction bottle to react, concentrating the solution under reduced pressure, and performing silica gel column chromatography separation, wherein the eluent is a mixed solution of ethyl acetate and petroleum ether, to obtain the naphthyl acrylate DOPO flame retardant.
2. The high-strength flame-retardant UV-curing adhesive according to claim 1, characterized in that: The ratio of the 6-DOPO-2-naphthol, 2,5-diacrylate phthalic acid and p-toluenesulfonic acid is (2-2.6) mol: 1 mol: (0.12-0.16) mol.
3. The high-strength flame-retardant UV-curing adhesive according to claim 1, characterized in that: The reaction temperature is controlled at 80-100°C and the reaction time is 4-10h.
4. The high-strength flame-retardant UV-curing adhesive according to claim 1, characterized in that: The active diluent is tripropylene glycol diacrylate or 1,6-hexanediol diacrylate; the photoinitiator is photoinitiator 1173 or photoinitiator 184; and the defoamer is an organic silicon defoamer.
5. The high-strength flame-retardant UV-curing adhesive according to claim 2, characterized in that: The preparation process of 6-DOPO-2-naphthol is as follows: 1,4-dioxane solvent, DOPO, 6-bromo-2-naphthol, tetrakis(triphenylphosphine)palladium and potassium carbonate are added into a microwave chemical reactor, reacted in a nitrogen range, the solution was concentrated under reduced pressure, and separated by silica gel column chromatography, the eluent was a mixed solution of dichloromethane and methanol, and 6-DOPO-2-naphthol was obtained.
6. The high-strength flame-retardant UV-curing adhesive according to claim 5, characterized in that: The ratio of DOPO, 6-bromo-2-naphthol, tetrakis(triphenylphosphine)palladium and potassium carbonate is 1 mol: (0.8-1.3) mol: (0.05-0.07) mol: (1.6-2.2) mol.
7. The high-strength flame-retardant UV-curing adhesive according to claim 5, characterized in that: During the reaction, the power of the microwave chemical reactor is controlled to be 300-600W, and the reaction time is 5-10min.
8. The high-strength flame-retardant UV-curing adhesive according to claim 2, characterized in that: The preparation process of the 2,5-diacrylate phthalic acid comprises the following steps: adding dichloromethane solvent, 2,5-dihydroxyphthalic acid and pyridine into a reaction bottle, dropping acryloyl chloride in an ice-water bath, reacting at 20-40° C. for 8-12 hours, concentrating the solution under reduced pressure, and performing silica gel column chromatography separation, wherein the eluent is a mixed solution of ethyl acetate and petroleum ether, to obtain 2,5-diacrylate phthalic acid.
9. The high-strength flame-retardant UV-curing adhesive according to claim 8, characterized in that: The ratio of the 2,5-dihydroxyphthalic acid, pyridine and acryloyl chloride is 1 mol: (2.2-2.5) mol: (2-2.4) mol.
10. A process for preparing a high-strength flame-retardant UV-curable adhesive as claimed in any one of claims 1 to 9, characterized in that: The preparation process is as follows: water, waterborne polyurethane acrylate, acrylate naphthyl DOPO flame retardant, active diluent and defoamer are added into a container, stirred and dispersed in a high-speed disperser, and then a photoinitiator is added to obtain a high-strength flame-retardant ultraviolet light-curing adhesive.
Citation Information
Patent Citations
Halogen-free flame-retardant polyurethane elastomer and preparation process
CN118108924B
